Neuropathic pain in diabetic patients: a review of pharmacological treatment selection according to psychopathological and somatic factors - Reginia, Artur; Mazur, Aleksandra; Bąba-Kubiś, Agata; Jabłoński, Marcin; Sołtysiński, Maciej; Samochowiec, Jerzy; Kucharska-Mazur, Jolanta (Frontiers in Psychiatry, 2026)
Diabetes and its complications are becoming an increasingly significant challenge for modern medicine. Diabetes carries a high risk of various complications, including neuropathic pain and certain mental disorders. It is important to note that these two types of complications often interact with each other. Neuropathic pain occurs in up to approximately 50% of patients and is much more common in those with poorly controlled diabetes. A characteristic feature of this type of pain is that it is usually chronic and resistant to conventional analgesics. This limits the available treatment options and necessitates the use of other medications, including certain psychotropic drugs. Among the most common psychiatric disorders are anxiety disorders, which affect about 18% of patients; depressive disorders, present in over 17% of individuals with type 2 diabetes; and sleep disorders, occurring in about 39% of patients. These complications require appropriate and comprehensive management, which cannot always be provided solely by specialists from specific medical fields. Furthermore, it is beneficial to use therapeutic strategies that combine efficacy in alleviating neuropathic pain with an effect on co-occurring psychiatric symptoms. Our search covered the last ten years, was conducted in the databases PubMed and ScienceDirect. The manuscript includes English-language publications, primarily review articles and recommendations that are as up-to-date as possible. The aim of this review is to present the principles of selecting pharmacological treatment for neuropathic pain in patients with diabetes, taking into account coexisting symptoms of depression, anxiety, and sleep disorders.